Feasibility Study And Investment Analysis Of Mix Use Sentraland Semarang - Soedarsono Soedarsono; Kartono Wibowo; Pramodya Pramodya (International Conference on Coastal and Delta Areas, 2017)
The construction of high-rise buildings is being done in urban areas, especially vertical buildings due to the low availability of land. The longer development of the building leads to more complex functions resulting from the fulfillment of needs for the surrounding community so that the development of the building that can accommodate all the needs of the community is the mix use building. Building with this combined function certainly has a more complex influence both in terms of economic and environmental. Required detailed economic calculations in order to obtain maximum results from the building, especially for investors who have invested for the construction of the building, for that needed a feasibility study and investment analysis. So before the project is carried out can be taken whether the project is feasible to do or not according to the results obtained calculations. The results of this study show that the feasibility study and investment analysis of mix use building that has been done can give a clear picture about the profit or loss of the project implementation for the owner who will invest or the building manager later. Keyword: Feasibility study, Investment analysis, Mix use building, Economic engineering